Changes in interleukin-1 beta induced by rTMS are significantly correlated with partial improvement of cognitive dysfunction in treatment-resistant depression: a pilot study. (July 2020) - Tateishi, Hiroshi; Mizoguchi, Yoshito; Kawaguchi, Atsushi; Imamura, Yoshiomi; Matsushima, Jun; Kunitake, Hiroko; Murakawa, Toru; Haraguchi, Yoshinori; Kunitake, Yutaka; Maekawa, Toshihiko; Kato, Takahiro A.; Asami, Toyoko; et al.
Highlights: Repetitive transcranial magnetic stimulation (rTMS) for the treatment of depression rTMS significantly improved depressive symptom scores rTMS significantly improved some subscales of cognitive dysfunction Changes in cognitive function and changes in IL-1β were significantly correlated Abstract: The impairment experienced by many individuals with depression is closely related to the cognitive symptoms of the disorder. Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive brain stimulation method that provides a promising technique for improving cognitive symptoms in treatment-resistant depression (TRD). It has recently been demonstrated that TRD is associated with increased inflammatory process. In the present study, we investigated whether a relationship exists between changes in cognitive function and those in inflammatory cytokines before and after rTMS treatment. Eleven patients with TRD were enrolled in a high-frequency (10 Hz) rTMS study. Cognitive function, depressive symptoms and serum concentration of inflammatory cytokines (interleukin (IL)-1β, IL-6 and tumor necrosis factor-α) were measured at baseline and at the endpoint of rTMS treatment. rTMS treatment significantly improved depressive symptom scores and some subscales of cognitive dysfunction. The present study has demonstrated that partial changes in cognitive function and changes in IL-1β were significantly correlated. The partial improvement of cognitive dysfunction by rTMS in the present study might be attributable to the reduction of peripheral IL-1β levels. The present results should be replicated for verification in future studies.